Application of novel AI-based algorithms to biobank data: uncovering of new features and linear relationships - Sherlock, Lee; Martin, Brendan R.; Behsangar, Sinah; Mok, K. H. (Frontiers in Medicine, 2023)
Using two large biobank databases in the public domain, we apply a novel AI-based algorithm to the NMR metabolomics data and map the metabolite matches to various biological pathways and focus on regions of localized enrichment as a measure of true activity. Through this, we accurately categorise phenotypes of interest to a high precision.